Volatile organic components of fresh leaves as indicators of indigenous and cultivated citrus species in Taiwan - Lin, S.Y., National Taiwan Univ., Taipei; Roan, S.F; Lee, C.L; Chen, I.Z (Bioscience, biotechnology, and biochemistry, 2010)
The volatile components of fresh leaves from 15 citrus species were investigated by headspace SPME with a GC-MS analysis. Three indigenous Taiwan citrus species, Citrus taiwanica, C. tachibana and C. depressa, were the major subjects. Eighty volatile organic compounds were detected as indicators of the genetic relationship. Linalool was the most abundant compound, and citronellal, geranial, neral, limonene and trans-β-ocimene were the major volatile compounds in fresh leaves. Linalool (56.37%) and myrcene (7.21%) were predominant in C. tawanica. An aldehyde-rich profile with citronellal (24.54%) contributed most to the aroma of leaves in C. tachibana, while Citrus depressa exhibited a high linalool/citronellal composition (23.56%/12.51%). The qualitative and quantitative patterns of the volatiles revealed that C. taiwanica was linked with sour orange, and either C. tachibana or C. depressa belonged to the mandarin group with C. tankan. Dendrograms also showed that the volatile patterns were related to the genetic classification.